Le Saint-Siège et les élites en Extrême-Orient : la création des universités catholiques de Pékin et de Tokyo, Fu-jen et Sophia (1908-1936) - Olivier Sibre (Les Cahiers de Framespa)
The Holy See is head of an international network of universities. The foundation of the universities Furen in Beijing and Sophia in Tokyo expresses the will of the Holy See to convert the elites of the westernized Far East, and to give to these institutions a real universal dimension, catholic, in front of the tensions between the missionary institutes and congregations, but also in front of the cultural et political strategies of the great powers towards the Christians missions. The comparative study of the two foundations from the end of the XIXth century to the beginning of the 1930’s try to bring out the different factors which influence the pontifical initiative within a “polycratic” government and a complex institution, while the popes describe their magister as a suprema et plena potestas.